Colorimetric determination of vitamin c in fresh and Dilute fruit juices and effect of thermal exposure On concentration at various stages - N.MADHAVI,; B.JYOTHI, (International Journal of Pharma and Bio Sciences, 2016)
Among all vitamins, vitamin C plays a crucial role in maintaining good health. In the present study ten types of fruits are analyzed to compare ascorbic acid levels and the effect of boiling on its quantity is also determined by colorimetric method .It is concluded that its levels are gradually decreased with increase of boiling time. Cheaply and mostly available fruits have higher concentration of ascorbic acid than other fruits. In Psidium guajana, Citrus aurantium and Phyllanthus emblica the concentration of vitamin C is more. It is concluded that the concentration of ascorbic acid is more in semi-ripened stage of the fruit than ripened and unripened stages of Citrus limon, Citrus aurantifolia and Psidium guajana. But it is more in unripened fruits of Citrus medica and Citrus aurantium. In Psidium cattleianum sabine and Psidium littorale ascorbic acid concentration is more in fully ripened stage.